The dark side of precrastination: exploring the psychological burdens of being too early - Gehrig, Christopher; Herzberg, Philipp Yorck (Frontiers in Psychology, 2025)
In today’s fast-paced world, where efficiency and immediacy are highly valued, one central question remains largely overlooked: When and why does early and swift action become a burden? This study focuses on the phenomenon of precrastination—the urge to complete tasks as early as possible—and sheds light on its “dark side.” Building on a recently proposed three-dimensional model of precrastination, we empirically examined the associations between anxiety- and compulsion-driven precrastination, chronic stress, and compulsive personality characteristics. In an online sample of adults (N = 200), anxiety-based precrastination was significantly associated with chronic stress, while compulsion-based precrastination correlated significantly with compulsive personality traits. Both subscales predicted their respective psychological correlates. These findings offer the first differentiated evidence that precrastination is not merely a sign of productivity but may also reflect maladaptive coping mechanisms. This opens a new perspective on a widely overlooked everyday behavior—and on the psychological costs that may come with acting too soon.